Pengaruh Parameter Eksternal Proses 3D Printing terhadap Kekuatan Tarik Hasil Cetak Filament PLA + - Alfidera, Mohammad; Finali, Asmar; Anam, Chairul; Fauzi Hanafi, Agung; Bhisma Wisnu Wardhana, Prabuditya (Jurnal Rekayasa Mesin, 2024)
In the industrial world, plastic is becoming increasingly popular alongside metal, especially in the field of research, thanks to the modernization of 3D printer usage. FDM (Fused Deposition Modeling) technology allows for the creation of 3D objects from digital models using additive manufacturing methods, with melted filament. This technology is popular due to its ease of use, low cost, environmental friendliness, and efficiency in product development. However, FDM products have weaker mechanical properties compared to injection molding because of weak points between the layers. Therefore, precise parameter settings are crucial to improving the tensile strength of the filament. Tensile testing is conducted to measure the strength of 3D printed products, showing that varying the printing orientation and layer height can enhance the mechanical properties of FDM objects. Research results indicate an average tensile strength of 28.5 MPa for ABS and 56.6 MPa for PLA, with elastic moduli of 1807 MPa and 3368 MPa, respectively. Further testing found differences in tensile strength among various combinations of Concentric and Rectilinear external patterns, with the Concentric pattern at 210°C producing the highest tensile strength of 61.49 MPa, and the Rectilinear pattern at 220°C producing the lowest tensile strength of 54.80 MPa. Comparative analysis shows that the Concentric pattern at 220°C has the highest ratio of 0.015, while the Rectilinear pattern at the same temperature has the lowest ratio of 0.0132. These results emphasize the importance of process parameter analysis to improve the tensile strength and material efficiency of 3D printed products.